J. S. Mill and his theory of international value, or international value - Кривуц, Юрий (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 1970)
Among the theories of international trade occupies a special place theory of comparative advantage of David Ricardo. These were supplemented and improved by many. With the unexpected position of its illuminated J. S. Mill, by constructing a theory of international value, or international value.